Shenling Baizhu Powder Inhibits RV-SA11-Induced Inflammation and Rotavirus Enteritis via TLR4/MyD88/NF-κB Signaling Pathway - Wang, Xiaoyan; Yang, Qian; Zhou, Xiaofeng; Chen, Ting; Dou, Liwen; Wang, Furong; Wang, Wei (Frontiers in Pharmacology, 2021)
Rotavirus enteritis (RVE) is a common acute intestinal infectious disease caused by rotavirus infection. It is an important cause of death in children younger than 5 years worldwide. Shenling baizhu powder (SBP), a classic traditional Chinese formulation, is one of the most popularly prescribed medicines for digestive diseases. Clinical studies have revealed the protective effects of SBP on RVE. However, the potential mechanism is still unclear. In this study, we aimed to evaluate the anti-rotavirus effect of SBP and its mechanism, focusing on the TLR4/MyD88/NF-κB signaling pathway. Our results demonstrated that, based on the inhibition of the virus-induced cytopathic effect in Caco-2 cells, the concentration for 50% of maximal effect (EC50) and selectivity index (SI) of SBP for RV-SA11 in the serum were 5.911% and 11.63, respectively. A total of 219 active compounds with oral bioavailability ≥30% and drug-likeness ≥ 0.18 were selected from the 10 ingredients present in the formulation of SBP, which acted on 471 potential targets. A total of 226 target genes of RVE were obtained from the GeneCards database. The protein-protein interaction (PPI) network showed that there was a close interaction between 44 common targets of SBP and RVE. The results of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that SBP acted on RVE through various inflammatory pathways and the intestinal immune network. Subsequently, we investigated the effect of SBP on TLR4/MyD88/NF-κB signaling pathway in vitro. After infection with RV- SA11, the expression of TLR4, MyD88, and NF-κB mRNA and protein increased significantly, which could be abolished by SBP treatment. In addition, the IL-1β, TNF-α, IL-6, and IFN-β levels increased markedly in Caco-2 cells infected with RV-SV11. Treatment with SBP partly reversed the changes of IL-1β, TNF-α, and IL-6, while further increased the level of IFN-β. In conclusion, our study revealed that SBP can significantly inhibit rotavirus replication and proliferation in vitro. The antiviral effect may be related to the regulation of the TLR4/MyD88/NF-κB signaling pathway, followed by the down regulation of inflammatory cytokines and up regulation of IFN-β induced by rotavirus.